Devaluation and the Cost of Living in the United Kingdom - Burtle, James L.; Liepe, Wolfram (Review of Economic Studies, 1949)
Journal Article Devaluation and the Cost of Living in the United Kingdom Get access James L. Burtle, James L. Burtle Geneva, Washington Search for other works by this author on: Oxford Academic Google Scholar Wolfram Liepe Wolfram Liepe Geneva, Washington Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 17, Issue 1, 1949, Pages 1–28, https://doi.org/10.2307/2295786 Published: 01 April 1949